1990
DOI: 10.7164/antibiotics.43.331
|View full text |Cite
|
Sign up to set email alerts
|

Placetins, platelet aggregation inhibitors from Streptomyces sp. Q-1043. I. Fermentation, isolation and biological properties.

Abstract: Placetins, platelet aggregation inhibitors were obtained from the culture broth of Streptomyces sp. Q-1043. These were designated placetins A, Al, B and Bl, respectively. Placetins A and B showed strong cytotoxicities against P388, L1210 and HeLa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Previous work had shown that this strain, when fermented using JNP1 medium, produced predominantly four aromatic amide compounds identified as toluene-2,4-dicarbamic acid dimethyl ester, toluene-2,4-dicarbamic acid diethyl ester, toluene-2,6-dicarbamic acid dimethyl ester, and toluene-2,6-dicarbamic acid diethyl ester . We found that when this strain was fermented using modified-RA medium and the extract was analyzed by HPLC-DAD-UV, an array of secondary metabolites with UV spectra characteristic of the angucycline class of antibiotics was observed. , In this paper, we report the fermentation, isolation, and structure elucidation of five new angucycline C -glycosides, grincamycins B–F ( 1 – 5 ), from S. lusitanus SCSIO LR32 along with the previously reported grincamycin ( 6 ). Moreover, we report the cytotoxicities of compounds 1 – 6 against the human cancer cell lines HepG2, SW-1990, HeLa, NCI-H460, and MCF-7 and the mouse melanoma cell line B16.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Previous work had shown that this strain, when fermented using JNP1 medium, produced predominantly four aromatic amide compounds identified as toluene-2,4-dicarbamic acid dimethyl ester, toluene-2,4-dicarbamic acid diethyl ester, toluene-2,6-dicarbamic acid dimethyl ester, and toluene-2,6-dicarbamic acid diethyl ester . We found that when this strain was fermented using modified-RA medium and the extract was analyzed by HPLC-DAD-UV, an array of secondary metabolites with UV spectra characteristic of the angucycline class of antibiotics was observed. , In this paper, we report the fermentation, isolation, and structure elucidation of five new angucycline C -glycosides, grincamycins B–F ( 1 – 5 ), from S. lusitanus SCSIO LR32 along with the previously reported grincamycin ( 6 ). Moreover, we report the cytotoxicities of compounds 1 – 6 against the human cancer cell lines HepG2, SW-1990, HeLa, NCI-H460, and MCF-7 and the mouse melanoma cell line B16.…”
mentioning
confidence: 80%
“…9 We found that when this strain was fermented using modified-RA medium and the extract was analyzed by HPLC-DAD-UV, an array of secondary metabolites with UV spectra characteristic of the angucycline class of antibiotics was observed. 10,11 In this paper, we report the fermentation, isolation, and structure elucidation of five new angucycline C-glycosides, grincamycins B−F (1−5), from S. lusitanus SCSIO LR32 along with the previously reported grincamycin (6). Moreover, we report the cytotoxicities of compounds 1−6 against the human cancer cell lines HepG2, SW-1990, HeLa, NCI-H460, and MCF-7 and the mouse melanoma cell line B16.…”
mentioning
confidence: 87%